2020
DOI: 10.3389/fphar.2020.00022
|View full text |Cite
|
Sign up to set email alerts
|

Limited Sampling Modeling for Estimation of Phenotypic Metrics for CYP Enzymes and the ABCB1 Transporter Using a Cocktail Approach

Abstract: Plasma concentration data points (n = 2,640) from 16 healthy adults were used to develop and validate limited sampling strategies (LSS) for estimation of phenotypic metrics for CYP enzymes and the ABCB1 transporter, using a cocktail of subtherapeutic doses of the selective probes caffeine (CYP1A2), metoprolol (CYP2D6), midazolam (CYP3A), losartan (CYP2C9), omeprazole (CYP2C19), and fexofenadine (ABCB1). All-subsets linear regression modelling was applied to estimate the AUC 0-12h for caffeine, fexofenadine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Two metrics were adopted to estimate CYP metabolic activity: the first was based on the ratio of plasma concentrations of probe/metabolite at 240 minutes after administration of metoprolol and omeprazole 33–35 . The second metric applied a limited sampling strategy (LSS) validated for subtherapeutic doses of omeprazole and metoprolol in Brazilians 36 . Briefly, the ratio of plasma concentrations of probe:metabolite at 90, 120 and 240 minutes were inserted into LSS linear regression equations to estimate the ratio of the area under the time‐concentration curves (AUC 0‐12h ) for metoprolol/α‐OH metoprolol and omeprazole/5‐OH omeprazole 36 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two metrics were adopted to estimate CYP metabolic activity: the first was based on the ratio of plasma concentrations of probe/metabolite at 240 minutes after administration of metoprolol and omeprazole 33–35 . The second metric applied a limited sampling strategy (LSS) validated for subtherapeutic doses of omeprazole and metoprolol in Brazilians 36 . Briefly, the ratio of plasma concentrations of probe:metabolite at 90, 120 and 240 minutes were inserted into LSS linear regression equations to estimate the ratio of the area under the time‐concentration curves (AUC 0‐12h ) for metoprolol/α‐OH metoprolol and omeprazole/5‐OH omeprazole 36 …”
Section: Methodsmentioning
confidence: 99%
“…The second metric applied a limited sampling strategy (LSS) validated for subtherapeutic doses of omeprazole and metoprolol in Brazilians 36 . Briefly, the ratio of plasma concentrations of probe:metabolite at 90, 120 and 240 minutes were inserted into LSS linear regression equations to estimate the ratio of the area under the time‐concentration curves (AUC 0‐12h ) for metoprolol/α‐OH metoprolol and omeprazole/5‐OH omeprazole 36 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We decided to use an abbreviated sampling protocol because single sampling points are already a standard procedure in cocktail studies 11 and abbreviated AUCs have already been suggested as suitable alternatives in modeling approaches. 14 Plasma was immediately separated by 10-minute centrifugation at 2500g (4°C) and stored at −20°C until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, some guidelines also refer to the cocktail study as an alternative evaluation method for DDIs. [11][12][13] Although cocktail studies can be used to assess CYP activities via a single trial and single administration only, multiple blood samples are required to evaluate the pharmacokinetics of a CYP probe drug. In recent years, for the purpose of reducing the burden on the subject, an evaluation method using a cocktail study in which the number of blood collections is reduced (limited sampling model) has been studied.…”
Section: Introductionmentioning
confidence: 99%